Análise filogenética dos Mesoeucrocodylia basais da América do Sul e a evolução do Gondwana (Archosauria: Crocodyliformes) - Avilla, Leonardo dos Santos (2002)
Mesoeucrocodylia includes the crocodylians usually divided in two groups - Mesosuchia and Eusuchia. Although the latter is mainly represented by living forms, today restrict to warm and wet habitats in the Tropics, the former includes a diverse set of forms, often found in sedimentary deposits from the main Mesozoic Brasilian basins. Many are the relationship hypotheses for the Mesoeucrocodylia. However, there is dispute between the phylogenetic relationships of the basal terrestrial groups, especially in regard to gondwanic forms (to those of Gondwanic distribution). lt is near a consensus between authors that gondwanic mesoeucrocodylia form a polyphiletic group. ln the present work, were analyzed 17 basal Mesoeucrocodylia taxa from the South American Mesozoic and Gondwanic related areas. An heuristic tree search under a maximum parsimony phylogenetic analysis revealed a single fully resolved relationship hypothesis to those taxa stressing the following conclusions. The Notosuchia forms a monophyletic group that includes a few monophyletic groups, highly supported under bootstrap analysis and Bremer indexes. The monophyly of the families Peirosauridae, Baurusuchidae, and Uruguaysuchidae were confirmed, although a few taxa were transferred to maintain monophyly. Three previously unrecognized groups were identified to maintain a monophyletic taxonomy. Brooks parsimony analysis was employed to investigate the relationships of the continental blocks derived from Gondwana. Contrary to previous authors propositions, the results indicate an isolated Africa during the Upper Cretaceous, while South America was linked to Antarctica, lndia, and Madagascar.